2021
DOI: 10.3389/fphar.2020.599022
|View full text |Cite
|
Sign up to set email alerts
|

Vanillic Acid Reduces Pain-Related Behavior in Knee Osteoarthritis Rats Through the Inhibition of NLRP3 Inflammasome-Related Synovitis

Abstract: Objectives: Synovitis plays an important role in knee osteoarthritis (KOA) pain. The activation of the NOD-like receptor protein 3 (NLRP3) inflammasome in fibroblast-like synoviocytes (FLSs) promotes KOA development. In this study, we aimed to investigate whether vanillic acid (VA), a monomer derived from Chinese herbal medicines, could target NLRP3 inflammasome-related synovitis to reduce pain.Methods: Rats in the KOA and KOA + VA groups were injected with monosodium iodoacetate (MIA) in the knee to induce KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…The top 40 pathways of KEGG results were visualized with a dot plot ( Figure 3(a) ). KEGG results indicated that the PI3K/AKT pathway [ 35 ], Toll-like receptor pathway [ 36 ], NOD-like receptor pathway [ 37 ], TNF pathway [ 38 ], and HIF-1 pathway [ 39 ] were closely related to OA. A network of 6 OA-related pathways and their corresponding targets is shown in Figure 3(b) .…”
Section: Resultsmentioning
confidence: 99%
“…The top 40 pathways of KEGG results were visualized with a dot plot ( Figure 3(a) ). KEGG results indicated that the PI3K/AKT pathway [ 35 ], Toll-like receptor pathway [ 36 ], NOD-like receptor pathway [ 37 ], TNF pathway [ 38 ], and HIF-1 pathway [ 39 ] were closely related to OA. A network of 6 OA-related pathways and their corresponding targets is shown in Figure 3(b) .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of inflammasomes, which are involved in the activation of GSDMD, prevents OA pathogenesis in various animal models [ 42 45 ]. Therefore, we determined the impact of GSDMD deficiency on the joints in the PTOA model induced by meniscal ligamentous injury (MLI).…”
Section: Resultsmentioning
confidence: 99%
“…The rats were divided into seven groups ( n = 5), labeled as groups A, B, C, D, E, F, and G. DEHP dosage was administered accordingly using the protocol by Zhang et al (2018) , while VA and VC dosage were administered accordingly using the procedure by Ma et al (2020) .…”
Section: Methodsmentioning
confidence: 99%